Serum Osmolality as a Predictor of Coronary Slow Flow Phenomenon - Ramy Raymond Elias (International Journal of the Cardiovascular Academy, 2025)
Background and Aim: Coronary slow flow (CSF) phenomenon is defined as a delay in the filling of epicardial coronary arteries in the absence of obstructive disease. Primary CSF phenomenon (PCSFP) is a noteworthy angiographic observation that should be regarded as a distinct clinical condition, although its precise pathophysiology is not yet fully understood. This study aims to investigate the correlation between serum osmolality and PCSFP in patients subjected to coronary angiography. Materials and Methods: This is a case-control study that included one hundred and twenty patients who presented to Ain Shams University. They were divided into two equal groups. Group A: patients who had PCSFP and Group B: patients with normal coronary flow. Results: Among PCSFP patients, the mean age was recorded as 54.53±11.6 years. Male sex was significantly associated with PCSFP, with an [odds ratio (95% confidence interval) of 2.582 (1.16-5.75)] and a P-value of 0.019. Among the traditional risk factors, smoking was markedly higher, contributing to 66.7% of the slow flow group of patients compared to 40% of the control group, with P-value = 0.003. PCSFP patients had increased hemoglobin and triglyceride levels, and both were strongly associated with PCSFP following multivariate analysis. A significant increase in serum osmolality was observed in PCSFP patients in comparison to control subjects. The calculated serum osmolality values were 295.08±6.77 mOsmol/kg in the PCSF group and 284.64±4.74 mOsmol/kg in the control group (P-value ≤ 0.001). Conclusion: PCSFP predominantly affects males with a history of smoking. Furthermore, hypertriglyceridemia, higher hemoglobin levels, and greater serum osmolality have been identified as independent predictors of its development.